The prevalence and beta lactam antibiotic susceptibility patterns of Staphylococcus aureus and Staphylococcus epidermidis isolated from healthy adult in IIUM Kuantan Campus - Abdul Halim, Nabila Huda; Ahmad Yusof @ Hanafi, Hanani (2017)
Staphylococcus species become one of the most important bacteria that cause many diseases. Some studies said that these organisms turn to develop resistance towards some of antimicrobial drugs include beta-lactam antibiotics. Resistant strain may spread through overcrowds such as in child care centres or school. There is lacking information on commensal Staphylococcus strains and their susceptibility patterns towards beta-lactam antibiotics isolated from healthy human skin especially among adult. Thus, this study was designed to measure the prevalence of commensal Staphylococcus strains specifically the Staphylococcus aureus and Staphylococcus epidermidis isolated from healthy human skin and to determine the antibiotic susceptibility pattern of beta-lactama antibiotics towards both strains. Swab sample was taken from palm of 24 healthy undergraduate students. Biochemical tests were performed to identify Gram positive bacteria, Staphylococcus aureus and Staphylococcus epidermidis. The antibiotic susceptibility patterns of the isolates were determine for two beta-lactam antibiotics (penicillin and ampicillin) by standard disk diffusion method. Eleven out of (68.75%) total 16 S. aureus are susceptible to both penicillin and ampicillin while 31.25% are resistant. Five out of total eight (62.5%) and 37.5% of S. epidermidis susceptible and resistant to both antibiotics, respectively. Penicillin and ampicillin are among the most effective antibiotic against Staphylococci. Regular surveillance and monitoring the antibiotic sensitivity pattern among community could facilitate the antimicrobial resistance spreading in the community.